Efeito da época e sistema de semeadura da Brachiaria brizantha em consórcio com o milho, sobre os componentes de produção e propriedades físicas do solo - Seidel, Edleusa Pereira; Schegoscheski Gerhardt, Ismael Fernando [UNESP]; Castagnara, Deise Dalazen; Neres, Marcela Abbado (Univ Estadual Londrina, 2014)
The objective of this study was to evaluate the development of Brachiaria brizantha- MG-4; sown in two seasons and two seeding systems in space between two rows, and to evaluate the effect of intercropping on maize yield, as well as evaluating the physical properties of the soil after the consortium. The experiment was conducted in the agricultural year 2010, the Municipality of Quatro Pontes/PR. The experimental design was randomized blocks as a factorial 2x2, and an additional treatment that was corn cultivation single, with four replications. The treatments consisted two intercropping systems: corn intercropped with Brachiaria brizantha in the row, and corn intercropped with Brachiaria brizantha in space between two rows, and two times of sowing Brachiaria brizantha: simultaneously corn, and twenty-five days after sowing corn. The seed was planted mechanically in no-tillage system, with spacing between the lines of 0,70 m. The ears were harvested by hand and in the laboratory were evaluated: yield components and productivity. Brachiaria brizantha- MG-4 was sown and harvested manually. We evaluated the production of fresh and dry mass and yield components. For soil analyzes the soil was sampled at 0-0.10 and 0,10-0,20 m. Were determined the total porosity, macroporosity and microporosity. The results demonstrated that the production components of Brachiaria brizantha were lower when it was sown twenty-five days after sowing corn, and between sowing systems when Brachiaria brizantha was sown in line. There was no reduction in grain yield of maize intercropped with Brachiaria system independent and sowing date. The consortium of pasture with corn increased the total porosity, and reduced soil bulk density.
Effect of time of sowing and system Brachiaria brizantha intercropped with maize on yield components and soil physical properties
Keywords: Cropping systems; grass; total porosity; bulk density soil